2019
DOI: 10.1111/bor.12422
|View full text |Cite
|
Sign up to set email alerts
|

Last Glacial Maximum glacier modelling in the Quemuqu Valley, southern Tibetan Plateau, and its climatic implications

Abstract: A well‐preserved Last Glacial Maximum (LGM) moraine set in the Quemuqu Valley on the eastern slope of the Qiongmu Gangri Peak offers great potential for reconstructing LGM glacier extent and examining LGM climate in the region. This study employed a coupled and physics‐based mass balance and ice‐flow model to investigate glacier sensitivities to climate in the valley. Based on the sensitivity tests and the well‐preserved LGM moraines, the study also reconstructed the LGM glacier extent in the valley and assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
(85 reference statements)
0
16
0
1
Order By: Relevance
“…The summer temperature was the dominant control on annual mass balance ultimately affecting glacier fluctuation in most of the glacial regions [48,49]. The previous approaches of glacier modelling in the TP also suggested that steady warming was more adequete factor on evolution of glaciers during various time periods [22,23]. The reason might be that the temperature is spatially more stable or homogeneous, less affected by topographic variations as compared to precipitation [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The summer temperature was the dominant control on annual mass balance ultimately affecting glacier fluctuation in most of the glacial regions [48,49]. The previous approaches of glacier modelling in the TP also suggested that steady warming was more adequete factor on evolution of glaciers during various time periods [22,23]. The reason might be that the temperature is spatially more stable or homogeneous, less affected by topographic variations as compared to precipitation [50].…”
Section: Discussionmentioning
confidence: 99%
“…The simple linear models provided dependency of numerical solutions on glacier geometry, and could be used to estimate the response of glacier across a wider range of parameter uncertainty [21]. Various dynamic and linear glacier models have been used to simulate the evolution of glaciers and prediction of glacier response to changing climate, which further highlights the impact of temperature and precipitation on the Tibetan Plateau [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, the A, B, and f values used in this study are 1.0 × 10 −7 a −1 kPa −3 , 1.5 × 10 −3 m a −1 kPa −2 , and .5, respectively (Plummer and Phillips, 2003;Refsnider et al, 2008). The DDF value is the main model parameter that controls the uncertainties on the model results owing to its larger variations compared with T s , on the Tibetan Plateau (Xu et al, 2020b). To test the effects of the DDF values on our model results, different DDF values (6-9 mm d −1 °C−1 ) were used to test the model sensitivity to changes in DDF.…”
Section: Coupled Mass Balance and Ice Flow Modelmentioning
confidence: 99%
“…Davide Tiranti, Agenzia Regionale per la Protezione Ambientale del Piemonte (Arpa Piemonte), Italy and Glasser, 2015; Xu et al, 2016;Xu et al, 2017a;Xu et al, 2017b;Xu and Yi, 2017;Eaves et al, 2019;Xu et al, 2020a;Xu et al, 2020b;Cui et al, 2020;Doughty et al, 2021).…”
Section: Access Edited Byunclassified
See 1 more Smart Citation